Open designettes, flowcharts, and pseudocodes in Python programming with the aid of Finch - YOONG, Cheah Huei (Institutional Knowledge at Singapore Management University, 2015)
Many universities around the world have introduced design in their engineering and computer-related curriculum.Design has played a role in student learning.Flowcharts and pseudocodes have been used in teaching computer programming and computational thinking.However,the combination of open designettes,flowcharts,and pseudocodes used to aid in teaching programming language are not investigated yet.In this paper,we have explored the teaching of Python programming language using open designettes,flowcharts,and pseudocodes in a series of weekly mini-projects with the help of a small,simple and educational programmable robot called Finch.Our studies revealed that these techniques have contributed positively to student learning and students' participation through observation,student participation rate and survey result.We believe the sharing of this experience in the paper will help academics and educators in the similar mission of enhancing students' learning in courses where students are from various countries and with different learning abilities.